Shifting Paradigms in the Study of Personality: A Retrospective Survey of Western Ideas Peralihan Paradigma dalam Kajian Personaliti Satu Tinjauan Retrospektif Idea Barat - Abdul Razak, Mohd Abbas; Hisham, Nik Ahmad (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
Abstract The birth of the Renaissance movement in the West ushered the scholars as well as the masses into a broader perspective of learning and knowledge seeking. The spirit of the Renaissance paved the way forward for scholars to gain freedom of speech and liberation from their old mindset. Europe that was bursting with new philosophical and scientific ideas also gave its people a wide range of perspectives in understanding man and personality. Secularism and modernism that came as a result of the Renaissance movement caused a shift in the understanding on man and his personality from a religious to a scientific one. In this study, the researchers would like to venture into the areas of man and personality from the Western perspective. Very precisely, the researchers would like to conduct a survey on the shifting paradigms in the field of Western psychology, pertaining to the study on man and personality. Upon performing the survey, the researchers would like to identify and analyze the underlying factors that caused the emergence of the different paradigms in Western psychology. Keywords: Shifting, Paradigms, Study of Personality, Retrospective, Survey, Western Ideas. ******************************************* Abstrak Kewujudan gerakan Renaissance di Barat mengiringi para ulama dan juga rakyat jelata ke perspektif pengajian dan pencarian ilmu yang lebih luas. Semangat Renaissance telah membuka jalan bagi ulama untuk memperoleh kebebasan untuk bersuara dan kebebasan daripada cara pemikiran lama mereka. Eropah penuh dengan idea-idea falsafah dan saintifik yang baru dan juga memberi rakyatnya pelbagai perspektif dalam pemahaman manusia dan personaliti. Sekularisme dan modenisme yang diakibatkan daripada pergerakan Renaissance yang menyebabkan peralihan pemahaman manusia dan keperibadiannya dari segi agama kepada segi saintifik. Dalam kajian ini, penyelidik ingin menerokai bidang manusia dan personalitinya daripada perspektif Barat. Secara tepat, penyelidik ingin menjalankan survei mengenai peralihan paradigma dalam bidang psikologi Barat, yang berkaitan dengan kajian manusia dan personalitinya. Setelah melaksanakan survei itu, penyelidik ingin mengenal pasti dan menganalisis faktor-faktor asas yang menyebabkan kemunculan paradigma yang berbeza dalam psikologi Barat. Kata Kunci: Iqbal, Falsafah Ego, Manusia, Kerohanian.